Rational Use of Mechanical Circulatory Support as a Bridge to Pediatric and Congenital Heart Transplantation - Leonardo A. Miana (Brazilian Journal of Cardiovascular Surgery)
Abstract Introduction: Donor shortage and organ allocation is the main problem in pediatric heart transplant. Mechanical circulatory support is known to increase waiting list survival, but it is not routinely used in pediatric programs in Latin America. Methods: All patients listed for heart transplant and supported by a mechanical circulatory support between January 2012 and March 2016 were included in this retrospective single-center study. The endpoints were mechanical circulatory support time, complications, heart transplant survival and discharge from the hospital. Results: Twenty-nine patients from our waiting list were assessed. Twelve (45%) patients were initially supported by extracorporeal membrane oxygenation (ECMO) and a centrifugal pump was implanted in 17 (55%) patients. Five patients initially supported by ECMO were bridged to another device. One was bridged to a centrifugal pump and four were bridged to Berlin Heart Excor®. Among the 29 supported patients, 18 (62%) managed to have a heart transplant. Thirty-day survival period after heart transplant was 56% (10 patients). Median support duration was 12 days (interquartile range [IQR] 4 - 26 days) per run and the waiting time for heart transplant was 9.5 days (IQR 2.5-25 days). Acute kidney injury was identified as a mortality predictor (OR=22.6 [CI=1.04-494.6]; P=0.04). Conclusion: Mechanical circulatory support was able to bridge most INTERMACS 1 and 2 pediatric patients to transplant with an acceptable complication rate. Acute renal failure increased mortality after mechanical circulatory support in our experience.